Evaluasi Kinerja Keuangan PT Telkom Indonesia Tbk Menggunakan Analisis Rasio, Komparatif, dan Common Size - Gita Aulia Mawardi; Dalizanolo Hulu (Fakultas Ekonomi dan Bisnis Islam, 2026)
Financial performance reflects a company’s ability to manage its financial resources to generate profits, meet its obligations, and ensure business sustainability. This study aims to analyse the financial performance of PT Telkom Indonesia (Persero) Tbk for the period 2020–2024 using financial ratio analysis, comparative analysis, and common-size analysis. The study employs a quantitative descriptive method using secondary data in the form of the audited annual financial statements of PT Telkom Indonesia (Persero) Tbk. The results of the study indicate that the company’s liquidity remains relatively low, as the current ratio and quick ratio were below 1 throughout the study period. Conversely, solvency showed improvement, marked by a decrease in the Debt to Assets Ratio (DAR) and the Debt to Equity Ratio (DER). Profitability fluctuated, showing a downward trend towards the end of the period, whilst operational efficiency remained relatively stable. A comparative analysis indicates that the company’s revenue has continued to rise year on year; however, profit growth has not always kept pace due to pressure from operating expenses. Meanwhile, common size analysis indicates an increasingly robust financial structure through an increase in the proportion of equity and a decrease in the proportion of liabilities, as well as the dominance of non-current assets, reflecting the capital-intensive nature of telecommunications companies. Based on these findings, the company needs to improve its liquidity management, control operating costs and optimise the utilisation of its assets in order to boost profitability and enhance the company’s value.